2018
DOI: 10.1002/jemt.23149
|View full text |Cite
|
Sign up to set email alerts
|

Hemorheological mechanisms for increased thrombosis in subjects using gestodene

Abstract: There are several possible mechanisms by which combined oral contraceptives (COC) use increase venous thromboembolism (VTE) risk. Melodene ® is a monophasic COC containing the third-generation progestin Gestodene (GSD), which is associated with increased risk of VTE.Therefore, the aim of this study was to investigate the possible alterations in viscoelastic parameters of whole blood and plasma clots along with the biophysical characteristics of erythrocytes and specifically fibrin fibers in females using a COC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…In this sense, the duration of contraceptive use as well as the generation of progesterone and the dose of estrogen in the COC have a clear influence on the risk of developing thrombosis. The risk of developing VTE is higher during the first 6 to 12 months after starting treatment, increasing from the fourth month of administration, but it is worth noting that the use of the third generation of progestins has a greater effect than the first (GIALERAKI et al, 2018;SWANEPOEL et al, 2018).…”
Section: Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, the duration of contraceptive use as well as the generation of progesterone and the dose of estrogen in the COC have a clear influence on the risk of developing thrombosis. The risk of developing VTE is higher during the first 6 to 12 months after starting treatment, increasing from the fourth month of administration, but it is worth noting that the use of the third generation of progestins has a greater effect than the first (GIALERAKI et al, 2018;SWANEPOEL et al, 2018).…”
Section: Developmentmentioning
confidence: 99%
“…There are alterations and an aggregation of erythrocytes, mainly by the combined DRSP/20EE® and DRSP/30EE®, accompanied by the spontaneous formation of a fibrin network that causes the occurrence of clots, which leads to occlusions in the vascular system. Therefore, the increased risk of VTE associated with these COCs can be explained by these clots rich in erythrocytes and fibrin that occlude the venous vessels (SWANEPOEL et al, 2018;EMMERSON et al, 2018).…”
Section: Developmentmentioning
confidence: 99%
“…Indeed, progestins may counteract the procoagulant effects of estrogen to varying degrees. Many studies 4,15,16 indicated that progestogens with a high androgenic potency, antagonize the risk of VTE associated with EE more than newer progestins [6][7][8] . For this reason, contraceptives containing EE associated with "nor" compound (levonorgestrel, norgestrel or norgestimate) record a threefold increase in the risk for a VTE event 2,17 , which rises to a sixfold increase when the contraceptive contains desogestrel, gestodene, drospirenone, or cyproterone acetate 2,6,7 .…”
Section: Introductionmentioning
confidence: 99%